2015
DOI: 10.1002/ece3.1500
|View full text |Cite
|
Sign up to set email alerts
|

Testing Taxon Tenacity of Tortoises: evidence for a geographical selection gradient at a secondary contact zone

Abstract: We examined a secondary contact zone between two species of desert tortoise, Gopherus agassizii and G. morafkai. The taxa were isolated from a common ancestor during the formation of the Colorado River (4–8 mya) and are a classic example of allopatric speciation. However, an anomalous population of G. agassizii comes into secondary contact with G. morafkai east of the Colorado River in the Black Mountains of Arizona and provides an opportunity to examine reinforcement of species' boundaries under natural condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 104 publications
(161 reference statements)
0
44
0
Order By: Relevance
“…Species with extralimital populations east of the river include two mammals ( Chaetodipus penicillatus , Ovis canadensis ), seven reptiles ( Chionactis annulata , Chionactis occipitalus , Crotaphytus bicintores , Gopherus spp. ; based on microsatellite data; Edwards et al, , Lichanura trivirgata , Phrynosoma platyrhinos , Uma scoparia ), two arachnids ( Smeringurus spp. Hadrurus arizonensis Clade III), and two insects ( Prodoxys sordidus, P. weethumpi ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species with extralimital populations east of the river include two mammals ( Chaetodipus penicillatus , Ovis canadensis ), seven reptiles ( Chionactis annulata , Chionactis occipitalus , Crotaphytus bicintores , Gopherus spp. ; based on microsatellite data; Edwards et al, , Lichanura trivirgata , Phrynosoma platyrhinos , Uma scoparia ), two arachnids ( Smeringurus spp. Hadrurus arizonensis Clade III), and two insects ( Prodoxys sordidus, P. weethumpi ).…”
Section: Resultsmentioning
confidence: 99%
“…These species also hybridize at the Mojave‐Sonoran ecotone east of the Mohave Valley (Figure b) where precipitation patterns are intermediate (Figure S1). In this contact zone the hybrids show an intermediate habitat preference to the two parent species (Edwards et al, ). The Ambrosia shrub (not studied here) has different drought mortality in the Mojave versus Sonoran deserts that is best explained by a natal precipitation index, also suggesting adaptation to different precipitation regimes (McAuliffe & Hamerlynk, ).…”
Section: Discussionmentioning
confidence: 99%
“…A third category, if coinciding with regions containing hybrids, might suggest that hybridized individuals select habitat in ways that are locally different than either of the two pure genotypes. Previous work has shown that these hybrids do occupy habitats with characteristics that span those of both their Mojave and Sonoran parental lineages in terms of topographic, surface textural and vegetation characteristics (Edwards et al, ). Our delineation of two categories does not counter these findings because here we explore local niche differences, that is local differences in species–environment relationships, rather than differences in occupied habitat as was explored by Edwards et al ().…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare niches of G. agassizii and G. morafkai , a common set of explanatory variables is needed; we therefore considered a set of 13 explanatory variables (Table ) that represented a suite of physiographic, vegetative and climatic characteristics hypothesized to influence the distribution of both species (Edwards et al, ; Inman et al, ; Nussear et al, ). These variables were chosen from among 18 by removing variables with Pearson's correlation values greater than 0.6 to reduce multicollinearity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation